Pengembangan Lembar Kerja Peserta Didik (LKPD) IPA Berbasis Literasi Sains pada Materi Perpindahan Kalor Kelas V SD Negeri 1 Pangkalpinang - Fitrahni, Imni; Feri Ardiansah; Erika Fitri Wardani (JBES (Journal Basic Education Skills), 2024)
This exploration is persuaded by the absence of science education situated showing materials of learning in schools. This review plans to foster showing materials as Understudy Worksheets (LKPD) in view of science education for 5th grade for move materials that are substantial and functional. This study utilized the Innovative work (Research and development) strategy with the ADDIE model adjusted from I Made Tegeh. The stages in this improvement are examination, plan, advancement, execution, and assessment. The subjects in this review were 26 understudies of class V SD Negeri 1 Pangkalpinang, comprising of 6 subjects for little gathering preliminaries and 20 subjects for huge gathering preliminaries. Information assortment strategies utilized were meetings and polls. Technical data analysis using descriptive quantitative data analysis was measured using the Likert and Guttman scales.The results of this study indicate that the students’ worksheet (LKPD) based on literacy-based science on heat transfer material obtain validity with a percentage of 94% which means very valid criteria perceived by a media expert, meanwhile, a material master apparent that the legitimacy of the worksheet is 88% which implies the worksheet is legitimate. The aftereffects of the little gathering preliminaries acquired a normal rate score of 96% with extremely viable standards. The huge gathering preliminary got a typical rate score of 98% with exceptionally down to earth measures. It tends to be reasoned that science education put together science worksheets with respect to warm exchange materials that have been created are substantial and useful as teaching materials in classroom learning.